2020
DOI: 10.1111/jbi.13985
|View full text |Cite
|
Sign up to set email alerts
|

Marine fish diversity in Tropical America associated with both past and present environmental conditions

Abstract: Aim Tropical America, including the Tropical Eastern Pacific and the Caribbean Sea, presents a high level of marine biodiversity, but its fish fauna has been poorly documented. In early studies marine species distributions were interpreted based on tectonic activity during the late Cenozoic, while more recent studies have highlighted a link with the present‐day environment. Here, we described the assemblage richness and composition of fishes in Tropical America and related these properties to both the past evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 86 publications
(111 reference statements)
2
7
0
Order By: Relevance
“…Performance indices for the empirical data set are lower than the ones on the simulated data due to a high number of false negatives (some due to the too stringent similarity threshold) and some false positives. It is likely that with an eDNA sampling limited to one day, all of the species present on site were not detected and that divers did not detect elusive or hidden species (Aglieri et al, 2020; Polanco et al, 2020). In order to reduce the number of false negatives and false positives, it would be necessary to extend the eDNA sampling of each site to several seasons and to consider similarity thresholds adapted for the taxonomic assignment.…”
Section: Discussionmentioning
confidence: 99%
“…Performance indices for the empirical data set are lower than the ones on the simulated data due to a high number of false negatives (some due to the too stringent similarity threshold) and some false positives. It is likely that with an eDNA sampling limited to one day, all of the species present on site were not detected and that divers did not detect elusive or hidden species (Aglieri et al, 2020; Polanco et al, 2020). In order to reduce the number of false negatives and false positives, it would be necessary to extend the eDNA sampling of each site to several seasons and to consider similarity thresholds adapted for the taxonomic assignment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that species have generally higher median area coverage in some regions compared with others (median area covered by the distribution of one species, Indomalayan=984 km2, Afrotropic=4’436 km2, Palearctic=4’805 km2, Neotropics=6’145 km2, Australasia=11’363 km2, Nearctic=16’455 km2), suggesting that tree species could have larger environmental niche width in some regions compared with others. Unlike previous large scale modelling efforts (Thuiller et al 2011), our approach combined both species distribution modelling and the geographic range limits, which can for instance represent dispersal limitations (Merow, Wilson, and Jetz 2017; Polanco et al 2020). Complementing previous local use of species distribution models to inform forest management (Booth 2018), our modelling synthesis provides a general approach to inform the suitability of potentially dominant and frequent species at local sites and provides structuring species for reforestation in the context of global restoration projects.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, maximizing the success of active ecosystem restoration and management initiatives across the globe requires fundamental information about which mixtures of species are best suited to surviving in those specific regions (Crouzeilles et al 2020). By combining species distribution modelling (Guisan and Zimmermann 2000) with spatial polygons to constrain the suitable area to the native range (Polanco et al 2020), we provide suitability for many tree species, beyond regions where species range maps are already available and broadly used by forester to manage forest resources (Caudullo, Welk, and San-Miguel-Ayanz 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the importance of historical and contemporary factors in shaping current beta diversity patterns, it is important to highlight the high percentage of unexplained inertia, which suggests that observed dissimilarities in taxonomic, phylogenetic and trait reef fish composition could also be explained by other processes, such as dispersal limitation. Indeed, it is worth noting that we did not explicitly consider the influence of dispersal processes associated to plate tectonics, which were found to be major drivers of tropical reef fish diversity worldwide (Leprieur, Descombes, et al, 2016; Polanco et al, 2020). Indeed, the isolation from the biodiversity centres that we used as a proxy for the influence of plate tectonics does not integrate the impact of soft and hard barriers to dispersal as well as stepping stones processes.…”
Section: Discussionmentioning
confidence: 99%